x = 3 + 2 3 − 2 , y = 3 − 2 3 + 2 , x 2 + x y + y 2 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Though all the solutions on this page are same,but i am upvoting your's one because of better representation, that's a skill
Bonus
: use \dfrac instead of \frac . It will look better.
example
:
dfrac
⇒
2
3
and
frac
⇒
2
3
Log in to reply
Thanks !! EDITED !!
And how can we represent 'implies that' and 'plus-minus sign'
Log in to reply
Input
: \Rightarrow
output
:
⇒
Input
: \pm
output
:
±
Rationalizing is the key word in such questions.
Exactly same solution
how you close the formula for [x+y]^2 there is only xy not 2xy. you need 2xy to close the formula of [x+y]^2.
Log in to reply
You can use the method of complete the square, to get this:
x^2 + xy + xy -xy + y^2
x^2 + 2xy + y^2 - xy
(x+y)^2 -xy
x 2 + x y + y 2 = ( x + y ) 2 − x y = ( 3 + 2 3 − 2 + 3 − 2 3 + 2 ) 2 − 3 + 2 3 − 2 × 3 − 2 3 + 2 = ( 3 − 2 ( 3 − 2 ) 2 + ( 3 − 2 ) 2 ) 2 − 1 = ( 2 ( 3 + 2 ) ) 2 − 1 = 1 0 0 − 1 = 9 9
Rationalize the denominator to get x = 5 − 2 6 and y = 5 + 2 6 . x 2 = 4 9 − 2 0 6 , y 2 = 4 9 + 2 0 6 and x y = 1 . So the value of x 2 + y 2 + x y = 9 9 .
Rationalizing the denominator :
x = 5 − 2 6
y = 5 + 2 6
x 2 + y 2 + x y = ( x + y ) 2 − x y = 1 0 2 − 1 = 9 9
@Dev Sharma You can display the square root symbol by using \sqrt{}.Put the radicand inside the { }.I have edited your solution.No need to worry :-)
Rationalise x and y Add and subtract xy in x²+y²+xy Then solve it
here note that, y=1/x; so given expression becomes =(x^2)+1+(1/x^2); also note ,x+y=x+1/x =10; now consider [x+1/x]^2=(x^2)+2+(1/x^2)= given expression+1;
so 100=given expression+1;
hence, given expression=99:
Problem Loading...
Note Loading...
Set Loading...
x = 3 + 2 3 − 2 = 5 − 2 6
y = 3 − 2 3 + 2 = 5 + 2 6
⇒ x 2 + x y + y 2
⇒ ( x + y ) 2 − x y
⇒ 1 0 2 − 1 = 9 9